Study on Antioxidant Property of Syzygium aromaticum (Clove) - Dahiru, Naziru; Paliwal, Ritu; Madungurum, Muhammad Abubakar; Abubakar, Abdurrahman Siraj; Abdullahi, Bilkisu (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This paper is aimed at evaluating the antioxidant properties of Eugenia Caryophyllata (Syzygium aromaticum), 100% aqueous and 20:80% (water and alcohol) for hydroethanolic and hydromethanolic extracts were prepared as working solutions for the studies. About 5 different antioxidant examinations of Syzygium aromaticum (Clove) extracts were carried out which include total phenolic content, antioxidant assay, free radical’s DPPH scavenging activity, scavenging hydrogen peroxide and reducing power assay, which was estimated spectrophotometrically by the use of butylated hydroxyanisole (BHA) as standard, and tocopherol used as the standard for reducing power test. Hydromethanolic extract exhibited higher free radical scavenging activity (62.12%), at the highest concentration of 1000 µg/mL followed by hydroethanolic and aqueous (58.80% and 48.32% respectively), less reducing power properties were observed with high absorbance value in the highest concentration of hydromethanolic extract (0.198 ± 0.001 A) and also hydromethanolic extract shows highest scavenging hydrogen peroxide (76.99 ± 0.09).